A new species of deep-sea anglerfish, genus Himantolophus (Lophiiformes: Himantolophidae) from the Andaman Sea, India - Rajeeshkumar, Meleppura; Pietsch, Theodore W.; Saravanane, Naryanane (Zootaxa, 2022)
A new species of the deep-sea ceratioid anglerfish genus Himantolophus is described from a single specimen collected off the east coast of the northern Andaman and Nicobar Islands, India, a member of the Himantolophus albinares-group, based in part on the absence of anterior escal appendages. The new species differs from other members of this group in having a unique illicial and escal morphology with a simple basimedial and a pair of basilateral filaments on the esca. The new species is compared with previously recognized members of the H. albinares-group.